Fiscal function of taxes, its impact on budget revenues at various levels - N. Z. Zotikov (Вестник университета, 2023)
Currently, in economics there is no single, well-established point of view on the number of functions performed by the tax. At the same time, all researchers are unanimous in their opinion that the main function is the fiscal function, according to which the revenue base of budgets of all levels is formed at the expense of taxes. All other functions: stimulating, regulating, etc. are closely related to the fiscal function. This function of taxes is used by the state in the development of tax policy at a particular stage of economic development. Based on official data, the article examines the impact of the fiscal function of taxes on the formation of budgets of the Russian Federation budget system for the period from 2006 to 2021. The author found that the state is currently pursuing a policy of fiscal federalism, which creates an imbalance in the revenue and expenditure parts of regional and local budgets.